Українсько-польські етномовні взаємини давнього періоду - Півторак, Г.П. (Мовознавство, 2020)
У статті розглянуто етнічні та мовні взаємини українців і поляків в історичній ретроспективі. Проміжне становище України між Польщею та Росією спричинилося до політичних спекуляцій щодо самобутності української нації та української мови. Відзначено, що російські великодержавні шовіністи вважали і вважають українців росіянами, які «ополячилися», а українську мову ― «російсько-польським діалектом», детально висвітлено основні етапи побутування цієї шовіністичної вигадки, підкреслено, що антинаукові твердження про українську мову поширювалися переважно через владні структури та на побутовому рівні, а не серед професійних філологів. З іншого боку деякі польські політики заявляли, що українці ― це поляки, які зазнали російського впливу. In this paper, the author discusses ethnic and linguistic relations between the
Ukrainians and the Poles, viewing them in historical retrospect. The intermediate position
of Ukraine between Poland and Russia gave rise to political speculations about the identity
of the Ukrainian nation as well as the Ukrainian language. Pointing out that adherents of
Russian imperialist chauvinism have considered the Ukrainians «Polonized Russians»,
and the Ukrainian language «a Russian-Polish dialec», he gives a detailed account of the
main periods of the history of this chauvinist fake and stresses that unscientific views
concerning Ukrainian have mostly been disseminated by authorities and have been spread
among the general public rather than professional philologists. On the other hand, some
Polish politicians claimed that the Ukrainians were Russified Poles.
Employing a viable scientific basis, the author elucidates prehistoric ethnic processes
in the Vistula-Oder and Dnieper areas and the stages of the parallel genesis of the Ukrainians
and the Poles as separate ethnic entities in the second half of the 1st millennium A.C. as well
the original identity of their respective languages. He shows that the right-bank Ukrainian
dialects were directly influenced by Polish only after the disintegration of Kyivan Rus’,
when Ukrainian territories were included in the Great Duchy of Lithuania and the Polish-
Lithuanian Commonwealth; the influence, however, was not strong enough to essentially
change the structure of Ukrainian. The author also gives detailed information on the mid-
19th century borrowing of Polish words, mostly scientific-cultural and technical terms,
emphasizing that these only came into the West Ukrainian, or Galician, variant of Standard
Ukrainian through artistic and scientific literature. These borrowings were then used in the
formation of unified Standard Ukrainian on the basis of Middle-Dnieper subdialects in the
first half of the 20th c. Coincidentally, the article highlights the reverse process that also took place at the
various stages of history, with the Polish language being influenced by the Ukrainian and borrowing numerous words from it.